A Simple Fight Decision Support System for BVR Air Combat Using Fuzzy Logic Algorithm - Khairul Ummah; Herlan Setiadi; Hisar Manongam Pasaribu; Dhani Anandito (Institut Teknologi Bandung, 2019)
Beyond Visual Range (BVR) air combat is a future trend of war tactic. In this situation, a fighter can attack the opponent before direct encounter. Its complexity arises due to the necessity to take into account the information of target’s maneuver, the specification of the missile, and the advantage of fighter position. In this paper, a simple BVR air combat system has been developed to give a fight strategy for pilot. Some important parameters are considered, such as the distance and the azimuth position of the target’s as well as the range and the energy of missile to reach the target. The information is processed to determine the fighter supremacy and the opponent’s threat factor. The result of the processing is used as an input of fuzzy logic algorithm to determine the optimal fighting strategy. The feasibility of the model and validity of the algorithm are verified by simulation under two typical situations